The Influence of Consumer Dissatisfaction and Variety Seeking on Brand Switching (A Study of Tumbler Tupperware Users in Surabaya) - Amirah Cetta Candraningtyas; Hery Pudjoprastyono (Management Science Research Journal, 2026)
This study aims to analyze the influence of consumer dissatisfaction and variety seeking on brand switching among users of Tupperware water bottles (tumblers) in Surabaya. The research method used was a quantitative approach with purposive sampling of 90 respondents who had used Tupperware and switched to another brand. Data collection was conducted via a questionnaire using a Likert scale, followed by analysis using Partial Least Squares (PLS-SEM). The results indicate that Consumer Dissatisfaction has a positive and significant effect on Brand Switching, with a coefficient of 0.338 and a p-value of 0.000. Additionally, Variety Seeking also has a positive and significant influence with a coefficient of 0.631 and a p-value of 0.000, and it is the more dominant variable in influencing Brand Switching. The research model explains 57.3% of the variation in Brand Switching.